The electrically conductive carbon nanotube (CNT)/cement composites for accelerated curing and thermal cracking reduction. (15th December 2016) - Kim, G.M.; Yang, B.J.; Ryu, G.U.; Lee, H.K.
Abstract: A functional cementitious composite for smart structures has attracted much attention due to their potential possibilities of application. In this paper, the accelerated curing and thermal cracking reduction with carbon nanotube (CNT)/cement composites are studied experimentally and theoretically. The heating element was fabricated by incorporation CNT into cement, and the cementitious composite block was placed in the middle of mortar samples. In order to generate and evaluate the heating performance, copper wires connected to the composite block were extended to a DC power supply. The variations of material characteristics including curing, thermal, electrical and mechanical properties of both the composite block and the sample were investigated. The experimental test results showed that the proposed curing was capable of improving the compressive strength by 40% at 24 h. In addition, based on the experimentally obtained material constants, a series of thermal analysis of mitigation level of thermal crack in larger scale were carried out. The electrically conductive CNT/cement composite block was found to be applicable to the cement mortar curing and reduction of thermal cracking of massive concretes structures.